Are 12 Years of Schooling Sufficient for Preparation for Tertiary Education? Evidence from the Reform of Secondary School Duration in Germany - Tobias Meyer; Stephan Thomsen (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
An important education reform in Germany reduced the duration of university preparatory schooling from 13 to 12 years, but left the curriculum unchanged. In the state of Saxony-Anhalt the reform was completed in 2007 with a double cohort of graduates, providing a natural experiment. We use primary panel data from this double cohort to evaluate the effects on success in tertiary education. Our findings show that the reform has heterogeneous effects on success in university education. Among others, students with only 12 years of schooling have some difficulties and skill deficits at university, but no higher drop-out probability.
Keywords: I21; J18; C21; 330